Polyphenol-rich extracts enhance growth, immune function, and antioxidant defense in juvenile rainbow trout (Oncorhynchus mykiss) - Mansoori, Aghil; Allaf Noveirian, Hamid; Hoseinifar, Seyed Hossein; Sajjadi, Mirmasoud; Ashouri, Ghasem; Imperatore, Roberta; Paolucci, Marina (Frontiers in Nutrition, 2024)
The present study was conducted to investigate the effects of a mixture of chestnut wood extract and olive extract (PMIX) rich in polyphenols on growth performance, hematological parameters, humoral and skin mucus immunity, hepatic antioxidant enzymes, and intestinal cytokine expression in rainbow trout (Oncorhynchus mykiss). Four diets containing 0 g PMIX kg -1 diet (group C-control), 0.5 g PMIX kg -1 diet (group P0.5), 1 g PMIX kg -1 diet (group P1), and 2 g PMIX kg -1 diet (group P2) were fed to triplicate groups of rainbow trout during an eight-week feeding trial. The feed conversion ratio was significantly improved by dietary PMIX supplementation. P0.5 and P1 significantly increased growth performance and protein efficiency ratio. P1 significantly decreased hepatosomatic and viscerosomatic indices. Hematological parameters exhibited no significant differences among the treatments, except significant elevations in monocyte percentage in P0.5 and P1. Serum lysozyme activity and blood respiratory burst activity significantly increased in all P groups. There were no significant differences in the blood phagocytic activity, phagocytic index, serum immunoglobulin, total protein, and bactericidal activity among groups. Skin mucus lysozyme activity significantly increased in P1, but there was no significant difference in mucus bactericidal activity among groups. Hepatic superoxide dismutase activity significantly increased in P1 and P2, but there was no significant difference in the hepatic catalase activity among groups. Intestinal interleukin-6 expression significantly increased in all P groups, whereas intestinal tumor necrosis factor-alpha exhibited upregulation in P1 and P2. Intestinal interleukin-1 beta expression significantly increased in P0.5. The present results suggest that polyphenols from chestnut wood and olive can boost growth performance, antioxidant capacity, and various immunological parameters of blood, skin mucus, and intestine of rainbow trout. Based on the results, supplementation of 1 g PMIX kg -1 diet is adequate to create such effects in rainbow trout.